The Dynamics of Studying Symbolism: Contextualizing the Russian Contribution within the European Tradition - Davydova, Olga S. (Actual Problems of Theory and History of Art, 2021)
The focus of the essay is on the scholarly tendencies which impacted the art historical study of Symbolism. Based on the unique practice and experience of the Russian specialists working under the aegis of the inter-institutional collective “European Symbolism and the Style Moderne”, “A Bibliographical Index: ‘Symbolism in the Visual Arts from the mid-19th to the First Decades of the 20th Century’” was completed in 2019. This was the first endeavour to compile and systematize art historical literature and source materials — published over more than a century — treating of Symbolism and visual culture. The underlying art historical criterion guiding the concept and composition of the Index and the actual selection of the bibliographical titles (assembled by Olga Davydova) was intended to reveal the global significance of the entries to the evolution of Symbolism and the Style Moderne and to emphasize those particular contents and thematic issues which had drawn scholars of Symbolism in twenty-two different countries. In turn, this helped us to observe the mechanisms which — from the standpoint of history and the theory of art — influenced the evolution of Symbolism worldwide. The contemporary, interdisciplinary approach followed during the compilation of the Index also enabled to focus attention not only on the study of Symbolism as an artistic phenomenon, but also on the issues of professional and methodological research within the area of art history. This is the first time that such an account examines the potential influence of Symbolism on the establishment of an analytical history of art — one beyond academic publications treating directly of the movement as a specific object of investigation.
Keywords: history and theory of art; bibliography; historiography; iconology; symbolism; art nouveau; fin de siècle; Russian and Western European art of the late 19th – early 20th century